Pengembangan Ketahanan Pangan Melalui Pemberdayaan Masyarakat di Kawasan Rawan Konflik Timika Papua - Rizal Syarief; . Sumardjo; Agit Kriswantriyono; Yulia Puspadewi Wulandari (Institut Pertanian Bogor, 2017)
Conflict handling in Papua so far is more often done with the repressive approach. The impact of conflict level is not decreasing, even international rejection is increasing. For that reason, a more humanistic approach is needed, including through empowerment. The purpose of this research is to study the community empowerment model in conflict-prone areas as an effort to realize the food security and the strategy of model replication in another area. The research method is done by action research, and SWOT analysis to formulate the strategy of model replication. The empowerment model conducted in several ways. First, gradually improve farming skills more productive-with the introduction of simple agricultural technology brings the change of community behavior from nomadic to the subsystem. Second, farming in order to provide for basic needs and also daily, weekly, monthly income as well as savings for families. Third, business development efforts by partnerships, with the government, companies, and religious institutions. The nodes of empowerment activities are conducted through the Agribusiness Training Center (ATC) that facilitates all empowerment activities. There are several things to consider in the replication model of empowerment: identification of program targets, needs assessment, institutional initiation, technology selection, assistance to the program, and partnerships with various stakeholders.